2006
DOI: 10.1209/epl/i2005-10501-8
|View full text |Cite
|
Sign up to set email alerts
|

Weak ergodicity breaking with deterministic dynamics

Abstract: The concept of weak ergodicity breaking is defined and studied in the context of deterministic dynamics. We show that weak ergodicity breaking describes a weakly chaotic dynamical system: a nonlinear map which generates subdiffusion deterministically. In the non-ergodic phase non-trivial distribution of the fraction of occupation times is obtained. The visitation fraction remains uniform even in the non-ergodic phase. In this sense the non-ergodicity is quantified, leading to a statistical mechanical descripti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
71
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 25 publications
(45 reference statements)
2
71
0
Order By: Relevance
“…separation of trajectories is sub-exponential, we have a strong indication that the usual Boltzmann-Gibbs statistical mechanics is not valid. Indeed it was found that certain systems with zero Lyapunov exponents break ergodicity [8,9]. Classical entropy theory is also not applicable in this case [6,7], particularly the entropy and average algorithmic complexity grow non linearly in time [7], while for a system with a positive Lyapunov exponent they increase linearly in time.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…separation of trajectories is sub-exponential, we have a strong indication that the usual Boltzmann-Gibbs statistical mechanics is not valid. Indeed it was found that certain systems with zero Lyapunov exponents break ergodicity [8,9]. Classical entropy theory is also not applicable in this case [6,7], particularly the entropy and average algorithmic complexity grow non linearly in time [7], while for a system with a positive Lyapunov exponent they increase linearly in time.…”
mentioning
confidence: 99%
“…Classical entropy theory is also not applicable in this case [6,7], particularly the entropy and average algorithmic complexity grow non linearly in time [7], while for a system with a positive Lyapunov exponent they increase linearly in time. Still the situation is not hopeless from the point of view of statistical mechanics and one may consider distributions of time average observables [8,9,10,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herein we shift the focus from variables to events, an event being a collision that may produce an abrupt change in the value of a variable. We assume these events to be the renewal, non-Poisson, and nonergodic events studied by Barkai and co-workers [8], that A B S and that the variable S has only two distinct values, S 1. Finally, we assume that the external perturbation changes the prescription that determines the times at which events occur, namely, the times at which the variable S may, or may not, change its sign.…”
mentioning
confidence: 99%
“…This final assumption reveals the lack of a Hamiltonian formalism, a condition shared by Refs. [5,7].We define the nonstationary autocorrelation function where t; t 0 is the waiting-time distribution density of age t 0 [8,9]. Note that Eq.…”
mentioning
confidence: 99%